Adaptive and fuzzy approaches for nodes affinity management in wireless ad-hoc networks - Natsheh, Essam; Tat, Chee Wan (IOS Press, 2008)
In most of the ad-hoc routing protocols, a static link lifetime (LL) is used for a newly discovered neighbors. Though this works well for networks with fixed infrastructures, it is inadequate for ad-hoc networks due to nodes mobility and frequent breaks of links. To overcome this problem, routing protocols with estimated LL using nodes affinity were introduced. However, these protocols also used the static estimated LL during the connection time. In contrast to that, in this paper two methods are presented to estimate LL based on nodes affinity and then continually update those values depending on changes of the affinity. In the first method, linear function is used to map the relationship between the signal strength fluctuation and LL. In the second method, fuzzy logic system is used to map this relationship in a nonlinear fashion. Significance of the proposed methods is validated using simulation. Results indicate that fuzzy method provides the most efficient and robust LL values for routing protocols.